Higher Incidence of Ischemic Stroke in Patients Taking Novel Oral Anticoagulants. Issue 12 (December 2018) - Shpak, Max; Ramakrishnan, Anurekha; Nadasdy, Zoltan; Cowperthwaite, Matthew; Fanale, Christopher
Abstract : Background and Purpose—: The increased use of novel oral anticoagulants (NOACs) to control atrial fibrillation is largely driven by the assumption that they are equally effective as warfarin at preventing ischemic stroke while putting patients at lower risk of hemorrhages. To test this hypothesis, a retrospective study of the relative incidence of strokes among patients taking NOACs versus those taking warfarin is performed. Methods—: Relative stroke incidence in the 2 groups of patients was compared using odds ratios and Fisher exact tests for significance using a data set of 71 365 on NOACs and 59 546 patients on warfarin. In addition, the 7033 patients with a record of both warfarin and NOAC use were analyzed as a separate cohort. Results—: There is a significantly higher (odds ratio=1.29, <0.001) frequency of ischemic strokes among patients prescribed NOACs compared with those on warfarin. The relative frequency of ischemic strokes was also higher for every individual NOAC compared with warfarin (these higher frequencies are statistically significant for dabigatran and apixaban, though not for edoxaban and rivaroxaban). There is a lower incidence of intracranial hemorrhages and nontraumatic hemorrhages in general among patients taking NOACs, consistent with the published literature. Comparisons of the demographic and clinical profiles of the patients taking NOACs to those on warfarin do not show significantly higher background stroke risk in NOAC patients; in fact, patients on NOACs tend to be at lower background risk overall for ischemic strokes. Conclusions—: Because NOAC use is associated with higher ischemic stroke risk together with a lower risk of hemorrhages than warfarin use, it can be concluded that patients on warfarin are more strongly anticoagulated. The observed effect could be a secondary consequence of dosage control or alternatively a result of different anticoagulant effects among the different medications. Abstract : Supplemental Digital Content is available in the text.